Chemical composition of soil evolving from municipal solid waste using energy dispersive X‐ray fluorescence. (17th April 2013) - Gupta, Dhrubajyoti; Roy, Subinit; Ghosh, Rita; Mitra, Ajoy Kumar; Streli, Christina; Markowicz, Andrzej
<x xml:space="preserve">Abstract</x> Municipal solid waste (MSW) generated in the city of Kolkata, India has been dumped at a site known as 'Dhapa', situated in the eastern fringes of the city, since the middle of 19th century. The soil in this area is expected to be evolving from several layers of dumped MSW through many decades. Earlier chemical composition study of surface soil of the site revealed the existence of heavy elements at comparatively higher concentrations than non‐contaminated soil. It becomes primary environmental prerogative to investigate further the bulk elemental composition of the soil at various depths. Samples from three different layers had been collected from six selected spots spanning a length of around 2 km, starting from the present core dumping area to a bypass highway dividing the rest of the city from Dhapa. Samples were studied first using radio‐isotope induced energy dispersive X‐ray fluorescence (RI‐EDXRF) spectrometer and later augmented by using a commercial (Epsilon 5, PANalytical B.V., Netherlands) high‐energy polarized‐beam variety (HE‐P‐EDXRF) to cover a wider range of heavy elements. In RI‐EDXRF, the backscatter fundamental parameter algorithm had been used with the readily available and/or preparable single elemental foils and/or compound pellets as calibration standards for elemental quantification. Whereas in the more sensitive HE‐P‐EDXRF, influence coefficient method was employed, which ideally requires several similar matrix geological soil standards. In the absence of optimum number of soil standards for HE‐P‐EDXRF, the RI‐EDXRF with backscatter fundamental parameter proved useful in covering the dynamic concentration range of certain important heavy metals in the MSW contaminated soil such as Cu, Zn, and Pb. NIST SRM 2586 comprising Pb contaminated soil was used for quality control. Potentially toxic heavy metals were observed at all levels (surface, middle, and lower with geometric mean concentrations in mg/kg) viz.: Cr (320, 250, 100); Ni (70, 70, 55); Cu(315, 320, 360); Zn (940, 810, 625); Cd (2.5, 1.8, 1.1); Sb (5.3, 8.9, 12.4); Ba (1050, 1050, 880); and Pb (530, 520, 724). There is a general trend of higher accumulation of Sb and Pb at lowest level, whereas there is a general trend of decrease with depth for Cr, Zn, and Cd. Copyright © 2013 John Wiley & Sons, Ltd.